EFEKTIFITAS PELAKSANAAN PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DI PROVINSI GORONTALO DALAM PERSPEKTIF HUKUM KEBIJAKAN PUBLIK - Dewi Panigoro, Candra; Tumuhulawa, Arifin; Kasim, Ramdhan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2023)
This study aims to find out about the implementation of the Complete Systematic Land Registration (PTSL) Program in Gorontalo Province from a public policy legal perspective and what obstacles affect the implementation of the Complete Systematic Land Registration (PTSL) program in Gorontalo Province. The method used in this writing is empirical juridical research, namely legal research regarding the enforcement or implementation of normative legal provisions directly in every particular legal event that occurs in society. The results of the study show that the Complete Systematic Land Registration Program (PTSL) is one of the efforts made by the government to respond to various public complaints, related to the procurement of making free certificates for poor people who own land or plots of land. PTSL, namely the land registration procedure for the first time, which is carried out simultaneously and simultaneously. In order to accelerate the implementation of the program, the Gorontalo Province National Land Agency coordinates with the district/city Land Agency in Gorontalo Province. The implementation is that officers go directly to the community, but the implementation so far cannot be said to have not met the target, because there are still many community lands that are still in registered status and have not been converted into certified land. One of the dominant factors constraining them is the lack of public awareness regarding the importance of land certificates as legal evidence for the land they own, limited competent human resources and inadequate infrastructure needed.